The Effect of Various Solvent in Soxhlet Extraction on The Characterictics of Basil Oil (Ocimum Americanum L.) - Luthfi Kurnia Dewi; Siska Dwi Setyawati; Annisa Nur Fidyanti Pamuji; Syifa Indrayana; Chandrawati Cahyani (Universitas Negeri Semarang, 2023)
Basil (Ocimum americanum L.) is a common plant in Indonesia used as the source of basil oil. Many methods to produce basil oil, such as solvent extraction using Soxhlet apparatus that called Soxhlet extraction. Determining solvent is a necessary factor in Soxhlet extraction because it affects the results of extraction in the form of quantity and quality of the essential oil produced. This shows that the selection of the type of solvent is an important factor to consider in the process of extracting basil essential oil, so this study was carried out to know the effect of solvent variations on the extraction results which were analyzed based on the yield and quality of essential oils including refractive index, specific gravity, and active compound. This research used three solvents with different polarities, ethanol, ethyl acetate and n-hexane. Basil leaves were separated from their flower and stem and dried in the oven at 102Â°C until their water content was 15-25%. Before extraction, dried basil leaves were cut to reduce size. The ratio of material to solvent that used was 1:50. Extraction was done at boiling point of each solvent for ten cycles. The rotary evaporator was used to separate basil oil and solvent. The highest yield is accomplished by basil oil that used ethanol (2,74%) followed by ethyl acetate (0,74%) and n-hexane (0,41%). The major active compounds obtained from each solvent were linalool 38.08% (ethanol), linalool 27.11% (ethyl acetate), and methyl chavicol 39.3% (n-Hexane). Basil oil from three solvents has a refractive index and specific gravity that suit commercial basil oil.